Pengaruh Struktur Modal, Kinerja Keuangan dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Liswatin, Liswatin; Pramadan Sumarata, Reksi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to determine the magnitude of the effect of Capital Structure, Financial Performance and Firm Size on firm value (study on manufacturing companies listed on the Indonesia Stock Exchange for the period (2015-2019). The results of this study indicate that the capital structure variable has a negative and insignificant effect on firm value, financial performance has a positive and significant effect, while firm size has a negative and significant effect.